Effect of urban morphology on thermal comfort in outdoor spaces: the case of the red village-El Kantara-Biskra - Sedira, Sara; Mazouz, Said (Journal of Applied Engineering Science & Technology, 2018)
Climate urban design is today a topical issue dealt with in many recent studies. This paper aims to test the influence of urban morphology on external climatic conditions and the urban microclimate by dealing with the quantitative aspects of thermal comfort and the assessment of the thermal environment from an objective point of view. This is based on an on-site investigation based on the correlation between the geometry of the street, its orientation and the evolution of the physical variables (Ta, Tg, HR, Va). The measures were the subject of a campaign carried out in the urban fabric of the Ksar of Dachra El- Hamra (the red village), the first nucleus of the city of El Kantara in the wilaya of Biskra. The objective is to define the most efficient urban geometry in terms of summer thermal comfort by studying the true impacts of urban form on solar control and microclimatic conditions in arid regions. The evaluation of the thermal comfort in these external spaces is carried out by analyzing the calculated physiological temperature (PET) values based on the measured microclimatic parameters. The analysis of the results obtained from the investigation enabled us to demonstrate the considerable effect of the sky view factor, calculated by Rayman Pro 2.1 software, on the thermal fluctuations in the street.